The Effect of Health Education on Infusion of Patients on Maintenance of Infusion Drops at Citama Hospital in 2021 - Rogayah, Rogayah; Al-Bahra, Al-Bahra; Dwi Lestari, Hernida (J I K O (Jurnal Ilmiah Keperawatan Orthopedi), 2022)
This study aims to identify the characteristics of patients who are infusions, before and after infusion health education is carried out on patients for the maintenance of infusion drops at Citama Hospital in 2021. This study uses a Quasi Experimental method with the research design "Pre and post test control group design" the conclusion of this study was obtained by comparing the effect of treatment on the group of subjects who were given the treatment. The research data was obtained based on a survey using a questionnaire to the sample at Citama Hospital. Based on the results of data analysis, there were 4 people (26.7%) who maintained the infusion drip before being given good health education and after being given the infusion health education, it showed an increase in the maintenance of the infusion drip, namely 12 people (80%). And maintenance of infusion drops before being given infusion health education was not good for 11 people (73.3%) and after being given infusion health education showed a decrease in infusion drip maintenance, namely 3 people (20%), where the analysis used a t-dependent test with the average result (0.533), standard deviation is 0.516 and p value 0.001 where p < 0.05, so it can be concluded that the health education of infusion in patients has a significant influence on the maintenance of infusion drops.